Development and Psychometric Assessment of the Parents\' Needs of Hospitalized Children Questionnaire - Nafiseh Zarei; Reza Negarandeh; Jamalodin Begjani; Elham Ghasemi; Mahboube Moradi (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: When a child is hospitalized, understanding and considering the needs of parents is as important as recognizing the needs of the child. Considering the critical importance of this subject, the present study aimed to design and assess the psychometric properties of the needs of parents with hospitalized children in Iran. Materials and Methods: The initial questionnaire was designed based on existing questionnaires and an extensive literature review. Face and content validity were assessed using two quantitative and qualitative methods. Construct validity was determined using the exploratory factor analysis approach in R-based Jamovi software. The reliability of the tool was determined by calculating the Cronbach's alpha coefficient and intra-cluster correlation coefficient. Results: In the qualitative review of face and content validity, the necessary changes were applied according to the expert panel's opinion. In quantitative content validity, three items were removed, and four items were revised. The content validity ratio (CVR) and the content validity index (CVI) of the whole questionnaire were obtained as 0.97 and 0.98, respectively. The questionnaire entered the construct validity stage with 38 items; 18 items were removed by exploratory factor analysis, and 20 remained. Kaiser-Meyer-Olkin test displayed the adequacy of sampling, and based on parallel analysis, six factors were extracted, which explained 46.8% of the variance. One factor that only included two items was removed, and finally, the extracted factors included "communication-based on respect," "comfort, "trust," "acquiring information," and "needs of family members" (all with four items). The intra-cluster correlation coefficient was 0.92, and Cronbach's alpha coefficient was 0.95. Conclusion: As evidenced by the results of this study, the under-study questionnaire for gauging parents' needs enjoys appropriate validity and reliability. It fits with Iranian cultural values and can be used to assess parents' needs.